2020
DOI: 10.21203/rs.3.rs-31477/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficits in Skilled Motor and Auditory Learning in a Rat Model of Rett Syndrome

Abstract: Background Rett Syndrome is an X-linked neurodevelopmental disorder caused by a mutation in the gene MECP2 . Individuals with Rett Syndrome display developmental regression at an early age, and develop a range of motor, auditory, cognitive and social impairments. Several studies have successfully modeled some aspects of dysfunction and Rett Syndrome-like phenotypes in transgenic mouse and rat models bearing mutations in the MECP2 gene. Here, we sought to extend these findings and characterize skilled learning,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…We compared four different experimental groups: normal rats (rattus norvegicus, n = 3, weights, Sprague Dawley, Harlan Labs, TX, USA), normal rats with pharmacologically altered inhibition, transgenic RTT rats (n = 4, weights, HET KO, SD-Mecp2tm1sage , Horizon Labs, MO, USA), and RTT rats with pharmacologically altered inhibition. The rat model of RTT we study here has been shown to recapitulate important dysfunctions and behaviors found in RTT humans including impaired motor functions [28][29][30] . Our goal was to quantitatively assess differences in three properties of these four experimental groups: body movements, neural activity, and the neuron-to-body relationship.…”
Section: Resultsmentioning
confidence: 91%
“…We compared four different experimental groups: normal rats (rattus norvegicus, n = 3, weights, Sprague Dawley, Harlan Labs, TX, USA), normal rats with pharmacologically altered inhibition, transgenic RTT rats (n = 4, weights, HET KO, SD-Mecp2tm1sage , Horizon Labs, MO, USA), and RTT rats with pharmacologically altered inhibition. The rat model of RTT we study here has been shown to recapitulate important dysfunctions and behaviors found in RTT humans including impaired motor functions [28][29][30] . Our goal was to quantitatively assess differences in three properties of these four experimental groups: body movements, neural activity, and the neuron-to-body relationship.…”
Section: Resultsmentioning
confidence: 91%